RhoA regulates peroxisome association to microtubules and the actin cytoskeleton - Schollenberger, Lukas; Gronemeyer, Thomas; Huber, Christoph Michael; Lay, Dorothee; Wiese, Sebastian; Meyer, Helmut E.; Warscheid, Bettina; Saffrich, Rainer; Peränen, Johan; Gorgas, Karin; Just, Wilhelm W. (PLOS ONE, 2010)
The current view of peroxisome inheritance provides for the formation of new peroxisomes by both budding from the endoplasmic reticulum and autonomous division. Here we investigate peroxisome-cytoskeleton interactions and show by proteomics, biochemical and immunofluorescence analyses that actin, non-muscle myosin IIA (NMM IIA), RhoA, Rho kinase II (ROCKII) and Rab8 associate with peroxisomes. Our data provide evidence that (i) RhoA in its inactive state, maintained for example by C. botulinum toxin exoenzyme C3, dissociates from peroxisomes enabling microtubule-based peroxisomal movements and (ii) dominant-active RhoA targets to peroxisomes, uncouples the organelles from microtubules and favors Rho kinase recruitment to peroxisomes. We suggest that ROCKII activates NMM IIA mediating local peroxisomal constrictions. Although our understanding of peroxisome-cytoskeleton interactions is still incomplete, a picture is emerging demonstrating alternate RhoA-dependent association of peroxisomes to the microtubular and actin cytoskeleton. Whereas association of peroxisomes to microtubules clearly serves bidirectional, long-range saltatory movements, peroxisome-acto-myosin interactions may support biogenetic functions balancing peroxisome size, shape, number, and clustering.
Gesehen am 27.06.2023